THERAPEUTIC EVALUATION OF CANNABIDIOL NANO-CREAM IN UVB-INDUCED PSORIASIS RAT MODEL - Aakashsinh Vaghela; Neeraj Sharma (Current Research in Pharmaceutical Sciences, 2025)
Psoriasis is a chronic inflammatory skin disease characterized by hyperproliferation of keratinocytes, immune cell infiltration, and erythematous plaques. This study aimed to evaluate the therapeutic efficacy of a cannabidiol (CBD) nano-cream in a UVB-induced psoriasis rat model. The nano-cream was formulated using a nanoemulsion-based system to enhance dermal delivery and sustained release of CBD. Characterization studies confirmed optimal pH, viscosity, spreadability, and high drug content. The anti-psoriatic potential was assessed by evaluating histopathological changes, Psoriasis Area Severity Index (PASI), and epidermal thickness in Wistar rats exposed to UVB radiation. Results demonstrated that the CBD nano-cream significantly reduced inflammation, erythema, and epidermal hyperplasia compared to control groups. The findings support the potential of CBD nano-cream as a promising topical therapeutic approach for the treatment of psoriasis.